Value creation strategies for health care: to deal with the epidemic of overuse in health care, patient preferences must be incorporated into the healthcare decision-making process, value creation must be calculated from a population health perspective, and a clear payment mechanism that provides incentives for value must be implemented - Weeks, Bill; Weinstein, James (Healthcare Financial Management, 2013)
In a recent article, Harvard University professor Michael E. Porter and Press Ganey CMO Thomas Lee outline a six-point strategy to improve healthcare value ("The Strategy that Will Fix Health Care," Harvard Business Review, October 2013). Although they offer several excellent ideas, their argument fails to address the epidemic of overuse.